The secret of teams what great teams know and do - Miller, Mark. (High bridge, 2011)
Teams are critical to the success of every organization. Departmental, interdepartmental, cross-functional, ad hoc, task-specific?teams do everything from planning the office party to setting the annual budget to establishing performance goals.
Keywords: Teams in the workplace